2009
DOI: 10.1074/jbc.m808667200
|View full text |Cite
|
Sign up to set email alerts
|

Activity of the Bile Salt Export Pump (ABCB11) Is Critically Dependent on Canalicular Membrane Cholesterol Content

Abstract: Mutations in ATP8B1 cause severe inherited liver disease. The disease is characterized by impaired biliary bile salt excretion (cholestasis), but the mechanism whereby impaired ATP8B1 function results in cholestasis is poorly understood. ATP8B1 is a type 4 P-type ATPase and is a flippase for phosphatidylserine. Atp8b1-deficient mice display a dramatic increase in the biliary extraction of cholesterol from the canalicular (apical) membrane of the hepatocyte. Here we studied the hypothesis that disproportionate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
95
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(99 citation statements)
references
References 31 publications
4
95
0
Order By: Relevance
“…This observation challenges a recently proposed model in which the morphological aberrancies and loss of ectoenzymes from the canalicular membrane in liver biopsies of Atp8b1 G308V/G308V mutant mice are primarily ascribed to a disruption of APL asymmetry, which would render the canalicular membrane hypersensitive to extraction of membrane sterols and proteins by hydrophobic bile salts. 21,33 Our current findings therefore imply that ATP8B1 serves a dual role. Besides catalyzing APLT activity, we propose that ATP8B1 may provide a molecular scaffold in the apical membrane to recruit structural components or modulators of the actin cytoskeleton involved in microvilli formation.…”
Section: Discussionmentioning
confidence: 71%
“…This observation challenges a recently proposed model in which the morphological aberrancies and loss of ectoenzymes from the canalicular membrane in liver biopsies of Atp8b1 G308V/G308V mutant mice are primarily ascribed to a disruption of APL asymmetry, which would render the canalicular membrane hypersensitive to extraction of membrane sterols and proteins by hydrophobic bile salts. 21,33 Our current findings therefore imply that ATP8B1 serves a dual role. Besides catalyzing APLT activity, we propose that ATP8B1 may provide a molecular scaffold in the apical membrane to recruit structural components or modulators of the actin cytoskeleton involved in microvilli formation.…”
Section: Discussionmentioning
confidence: 71%
“…Fourth, cholesterol is a critical component of lipid microdomains. Feeding mice lacking Atp8b1 with a cholate diet renders them cholestatic and markedly reduces the cholesterol to phospholipid ratio in cLPM [29]. These and other authors have shown that the activity of Bsep depends on membrane cholesterol content [29,30].…”
Section: Discussionmentioning
confidence: 97%
“…BSRMs contain the transporters required for canalicular bile formation and are enriched in cholesterol. The function of the ABCtransporters is modulated by membrane cholesterol, since a positive correlation between membrane cholesterol content and transporter activity for Bsep [30], BCRP [32] and MRP2 (Guyot and Stieger unpublished) expressed in Sf9 cells and for Bsep in cLPM [29] has been demonstrated. Stimulation of Mrp2 will increase BS independent bile flow and consequently lower BS concentration in the canaliculus.…”
Section: Discussionmentioning
confidence: 99%
“…ATP8B1 mutant mice display a dramatic increase in biliary output of canalicular cholesterol. Subsequent studies have shown that the activity of the bile salt pump is crucially dependent on the cholesterol content of the canalicular membrane (Paulusma et al, 2009). The exoplasmic leaflet of this membrane is rich in sphingolipids that are tightly packed with cholesterol to provide maximum resistance against the detergent action of hydrophobic bile salts.…”
Section: Apical Barrier Functionmentioning
confidence: 99%